Value congruence and consumer’s satisfaction towards online banking –the mediation role of affective commitment - Rahman, Muhammad Sabbir; Nazrul, Islam (Editura Economica, 2015)
Value congruence (VC) and its impact on customers’ satisfaction towards online banking practices rarely appear in the literature of services marketing. The aim of this inquiry is to explore the influence of VC towards customer’s satisfaction towards online banking and examine the mediating role of affective commitment in the Bangladeshi online banking service context. This research applied survey method for the accumulation of information. Data was analysed by means of descriptive statistics followed by exploratory factor analysis, confirmatory factor analysis and structural equation modelling. The findings uncovered that the positive impact of VC on customers’ satisfaction is stronger when affective commitment play as a mediating function. This research also found evidence that increasing service quality to optimise customers’ satisfaction in this sector is not enough since the mangers need to concentrate on customers’ perceived value, as well as to design the services that are truly perceived by their customers.